Perilaku Hemat Energi Ibu Rumah Tangga Di Perumahan Azhar Kelurahan Azhar Permai Kecamatan Talang Kelapa Kabupaten Banyuasin - Nurhayati, Nurhayati; Husin, Azizah; Saputra, Ardi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research aims to determine the energy saving behavior of housewives in Azhar Housing, Azhar Permai Village, Talang Kelapa District, Banyuasin Regency. The research uses a quantitative approach with a percentage descriptive method. Data collection techniques use questionnaires. With a total research sample of 80 housewives. The results of the research show that the energy saving behavior of housewives in Azhar Housing, Azhar Permai Village, Talang Kelapa District, Banyuasin Regency obtained an average figure of 77% with good criteria with the following details. First, the behavior of housewives in reducing energy use has been very good, as evidenced by the percentage figure of 82%. Second, the behavior of housewives in maintaining equipment that uses energy has also been shown to be good with a percentage figure of 74%, which means it is classified as good. Third, in their behavior of using alternative and environmentally friendly energy sources, housewives obtained a percentage figure of 74%, which means they are included in the good category.